A high throughput screening assay for identifying glycation inhibitors on MALDI-TOF target. (1st March 2015) - Zhang, Qiuting; Tu, Zongcai; Wang, Hui; Fan, Liangliang; Huang, Xiaoqin; Xiao, Hui
Highlights: A high throughput screening assay for glycation inhibitors was proposed. The new analysis method was base on the MALDI-TOF mass spectrometry. The method is rapid and time-saving for reaction on the MALDI plate. DSP, inhibition and IC50 can be used to evaluate the inhibition of inhibitors. Abstract: The Maillard reaction plays an important role in the food industry, however, the deleterious effects generated by the advanced glycation end-products (AGEs) have been well recognized. Many efforts have been made to seek new AGE inhibitors, in particular those natural ones without adverse effect. We have developed a rapid, mass spectrometry based, on-plate screening assay for novel AGE inhibitors. The glycation reaction, inhibition feedback as well as the subsequent MALDI mass spectrometric analysis occurred on one single MALDI plate. At 1:10 M ratio of peptide to sugar, as little as 4 h incubation time allowed the screening test to be ready for analysis. DSP, inhibition and IC50 were calculated to evaluate selected inhibitors and resulting inhibition efficiencies were consistent with available references. We demonstrated that this method provide a potential high throughput screening assay to analyze and identify the anti-glycation agents.